Strategi Pengembangan Usaha Peternakan Sapi Perah Berkelanjutan Melalui Adaptasi dan Kreativitas Wirausaha pada Anggota KPBS Pangalengan - Aditya Faturahman; Adi Bil Haq; Delia Fazriah Nursyifa; Nesa; Rasya Putri Falisha; Itto Turyandi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to analyze sustainable dairy farming development strategies among members of the South Bandung Livestock Cooperative (Koperasi Peternak Bandung Selatan/KPBS) Pangalengan by examining business adaptation and entrepreneurial creativity as key drivers of business sustainability. A qualitative descriptive approach was employed. Primary data were collected through in-depth interviews, field observations, and documentation involving selected KPBS members, while secondary data were obtained from cooperative reports, government publications, and relevant scientific literature. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña through data reduction, data display, and conclusion drawing, with data credibility ensured through source and technique triangulation. The findings reveal that business sustainability is supported by farmers' adaptive capacity in feed management, milk quality improvement, the adoption of simple farming technologies, business diversification, and the use of digital media to access market and technical information. Entrepreneurial creativity is reflected in feed innovation, the utilization of livestock waste into organic fertilizer, the development of value-added dairy products, and collaborative initiatives among cooperative members. Furthermore, KPBS plays a strategic role in strengthening business sustainability through marketing support, production inputs, veterinary services, and farmer capacity building. The study contributes to the sustainable agribusiness literature by demonstrating that business adaptation, entrepreneurial creativity, and cooperative institutional support constitute an integrated framework for strengthening the sustainability of smallholder dairy farming. These findings provide practical implications for cooperatives and policymakers in designing farmer empowerment, entrepreneurship development, and technology adoption programs to improve the long-term competitiveness of dairy farming.